2021
DOI: 10.1371/journal.pgen.1009931
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-specific ERBB3 deletion results in a genetic background-dependent increase in intestinal and colon polyps that is mediated by EGFR

Abstract: ERBB3 has gained attention as a potential therapeutic target to treat colorectal and other types of cancers. To confirm a previous study showing intestinal polyps are dependent upon ERBB3, we generated an intestinal epithelia-specific ERBB3 deletion in C57BL/6-ApcMin/+ mice. Contrary to the previous report showing a significant reduction in intestinal polyps with ablation of ERBB3 on a B6;129 mixed genetic background, we observed a significant increase in polyp number with ablation of ERBB3 on C57BL/6J compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Rare NRG1 gene fusions have, however, been identified as potential oncogenic drivers in CRC ( Jonna et al, 2019 ). In mouse models of intestinal tumorigenesis, deletion of Erbb2 and Erbb3 has been reported to both increase and decrease the tumor burden, depending on the genetic background ( Rojas et al, 2021 ). Our data from two independent sources showed that high stromal NRG1 expression correlates with improved survival in CRC, suggesting that in most CRCs, high stromal NRG1 expression is in fact beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Rare NRG1 gene fusions have, however, been identified as potential oncogenic drivers in CRC ( Jonna et al, 2019 ). In mouse models of intestinal tumorigenesis, deletion of Erbb2 and Erbb3 has been reported to both increase and decrease the tumor burden, depending on the genetic background ( Rojas et al, 2021 ). Our data from two independent sources showed that high stromal NRG1 expression correlates with improved survival in CRC, suggesting that in most CRCs, high stromal NRG1 expression is in fact beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials with inhibitors blocking ERBB3 had little to no efficacy in the colon and showed a tendency toward promoting tumor progression (24). A subsequent preclinical robustness assay using different genetic backgrounds showed that deletion of Erbb3 results in a significant reduction in polyp number when performed on a 129S1/SvImJ background, but increased polyp number in B6J mice (25). These studies suggested that the outcomes of ERBB3 clinical trials would have been predicted using a robustness assay, which could have led to a more informed clinical trial.…”
Section: Origin Of Translational Failuresmentioning
confidence: 99%